The effect of low-temperature heat treatment on hydrogen embrittlement of sheared edge in advanced high-strength steels - Jisung Yoo; Yonghee Jo; Jin-Jong Lee; Tae-Ho Lee; Chang-Hoon Lee; Jiyoung Kim; Seung-Pil Jung; Yeoung-Chul Park; Hyungkwon Park (Journal of Materials Research and Technology)
Hydrogen embrittlement (HE) has become an important issue in ultra-strong automotive steel applications. This study investigated the HE mechanism of the sheared edge in complex phase (CP) steel and examined the HE improvement achieved via low-temperature soaking (150 °C). To this end, changes in the microstructures of both the steel matrix and sheared edge were analyzed, and various mechanical properties were evaluated before and after soaking. In addition, the HE resistances of the steel and sheared edges were evaluated using slow-strain-rate tensile and immersion tests, respectively. Before soaking, the CP microstructure comprised of tempered martensite and lath bainite with island-shaped polygonal bainite. After soaking, the overall microstructure remained largely unchanged, the yield strength and fracture toughness increased, and uniform localized nanohardness was achieved through carbon redistribution. The intrinsic resistance to HE is enhanced by carbon clustering or carbide precipitation, which impedes hydrogen diffusion. Immersion tests revealed that HE occurred only in the sheared edge with a burr upward, indicating the cut-edge condition significantly affected HE susceptibility. H-induced cracks in the CP microstructure before soaking propagated along interfaces between the island bainite and the matrix, where stress concentration occurred because of large differences in nanohardness. After soaking, cracks penetrated the island bainite, suggesting a reduced stress concentration caused by the more uniform nanohardness across phases. Overall, soaking improved the HE resistance of the sheared edge by altering crack propagation behavior. The enhanced fracture toughness improved damage tolerance to pre-existing defects and enhanced the resistance to HE, along with reduced H diffusivity.